2018
DOI: 10.5194/esurf-6-903-2018
|View full text |Cite
|
Sign up to set email alerts
|

Initial insights from a global database of rainfall-induced landslide inventories: the weak influence of slope and strong influence of total storm rainfall

Abstract: Abstract. Rainfall-induced landslides are a common and significant source of damages and fatalities worldwide. Still, we have little understanding of the quantity and properties of landsliding that can be expected for a given storm and a given landscape, mostly because we have few inventories of rainfall-induced landslides caused by single storms. Here we present six new comprehensive landslide event inventories coincident with well identified rainfall events. Combining these datasets, with two previously publ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
130
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(146 citation statements)
references
References 76 publications
13
130
2
1
Order By: Relevance
“…Our finding regarding similar cutoff values obtained from different inventories created for the same area also supports this argument. This conclusion is also supported by Marc et al (2019), who found similar beta values between ETLs and RTLs, but the cutoff value is much smaller because a correction to remove runout was applied.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…Our finding regarding similar cutoff values obtained from different inventories created for the same area also supports this argument. This conclusion is also supported by Marc et al (2019), who found similar beta values between ETLs and RTLs, but the cutoff value is much smaller because a correction to remove runout was applied.…”
Section: Discussionsupporting
confidence: 64%
“…Dahal and Hasegawa (2008) used a dataset of 193 landslides occurring from 1951 to 2006, part of which were from the Koshi River basin, to generate a threshold relationship between rainfall intensity, rainfall du-ration and landslide initiation. The latest research from Marc et al (2019) gives the magnitude of annual landsliding in different High Himalayan valleys.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations